Observation of alate swarming and colony foundation in Syntermes spinosus (Isoptera: Termitidae) in Amazonia - Martius, Christopher (Sociobiology, 2001)
Flight phenology, mating behavior, colony foundation and the architecture of the initial "royal chamber" of alates of Syntermes spinosus, a common Central Amazonian leaf-feeding, soil-inhabiting termite, are described. Alate swarming occurs throughout the year, and is probably related to rainfall. The alates of this species dig the initial chamber directly into the soil.